Self-Management and Relating Factors among Chronic Kidney Disease Patients on Hemodialysis: An Indonesian Study - Fitri Mailani; Rahmi Muthia; Emil Huriani; Rahmiwati Rahmiwati (Department of Nursing, Faculty of Medicine, Diponegoro University, 2023)
Background: The latest approach to managing chronic kidney disease (CKD) involves the implementation of self-management methods. Nonetheless, numerous previous studies indicate that self-management behaviors remain inadequate among hemodialysis patients in Indonesia. Therefore, a deeper comprehension of the factors that affect a patient’s self-management should be studied.Purpose: This study aimed to examine self-management among CKD patients undergoing hemodialysis and its relating factors.Methods: The study used a cross-sectional approach. A convenience sample of 164 patients undergoing hemodialysis determined using a table of power analysis was recruited from two hemodialysis centers in Padang, Indonesia, from May to July 2022. Hemodialysis self-management instrument-18 (HDSMI-18), the scale of self-efficacy for chronic diseases, and the hemodialysis knowledge questionnaire were used as the instruments. T-tests, ANOVA, Spearman correlation test, and multiple linear regression were used to analyse the data.Results: Self-management, knowledge, and self-efficacy mean scores were 48.62(8.45), 17.77(2.96), and 43.05(10.08), respectively. There was a significant positive correlation between self-management with education (p=0.000), employment status (p=0.025), monthly income (p=0.003), knowledge (p=0.000), and self-efficacy (p=0.004). Multiple linear regression analyses for overall self-management indicated that knowledge and education were the main influencing factors of self-management.Conclusion: Hemodialysis patients had a subpar degree of self-management. Furthermore, knowledge and education were the most significant influencing factors of self-management. Nurses are expected to be able to provide structured education to increase patient knowledge which will later yield good self-management.